Gambaran Intervensi Family Centered Care pada Pasien Balita di RS Perkebunan Wilayah Karesidenan Besuki Raya - Yeffri Dwi Fradika; Lantin Sulistyorini; Dini Kurniawati (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
The implementation of family-centered care in pediatric hospitals in developed countries has been well-standardized. But, in Indonesia, it can be implemented with the possibility to be realized ideally is not easy because of many health workers do not understand family-centered care properly. The purpose of this study is to describe the application of Family Centered Care in toddler patients in inpatient rooms conducted by nurses. This research is a descriptive study with a cross-sectional approach using a purposive sampling technique. The study was conducted at Kaliwates General Hospital, Jember Klinik Hospital and Elizabeth Situbondo Hospital Data collection was performed using a Family Centered Care questionnaire. Data Collection was carried out from September 2019 to December 2019. The study Participants were 98 families selected by purposive sampling technique. Data were collected techniques using in-depth interviews and documentation. The results showed that the majority of families (83.7%) were good. Nurses can be good counselors and educators in meeting the needs of families and children in the hospital to have a good cooperative relationship between family and nurses. Nurses can improve the quality of their services by understanding more deeply about family needs and strengths.